PROSPECTS OF Toll-LIKE RECEPTOR AGONISTS AND ANTAGONISTS FOR PREVENTION AND TREATMENT OF VIRAL INFECTIONS - A. A. Nikonova; M. R. Khaitov; R. M. Khaitov (Медицинская иммунология, 2019)
Antiviral research has focused mainly on viral targets. However, cellular targets involved in the viral life cycle and antiviral response are becoming more attractive for research, providing a variety of opportunities for antiviral therapy. Toll-like receptors (TLR) play an important role in activation of both innate and adaptive immune systems, including a response to respiratory viral infections. In this review we shall discuss TLRs as potential targets for development of novel antiviral drugs including the mechanisms for induction the antiviral response by means of type I interferon production, as well as viral evasion strategies. In addition, we describe several new molecules that have been applied as TLR agonists or antagonists. The safety issues are also discussed.